La posizione dei pronomi clitici nella ristrutturazione: variazione diatopica e diacronica in italo-romanzo - Cardinaletti, Anna; Giusti, Giuliana (Verbum – Analecta Neolatina, 2025)
In Italian and Italo-Romance dialects, the position of clitic pronouns in restructuring sentences is subject to variation. Like Italian, the northern, Tuscan, and median Italo-Romance dialects show both cliticization on the finite verb (clitic climbing) and enclisis on the infinitival verb, while the southern dialects have mandatory clitic climbing. Some differences between the AIS data, dating back to one century ago, and the contemporary dialectal data with regard to clitic climbing in northern dialects are attributed to the data collection methods and not to a recent diachronic change extending climbing towards the North. A new data collection method, specially designed to detect optionality, provides a more nuanced picture of language variation and suggests that the innovation of enclisis is starting to affect the southern Italo-Romance dialects.